Evaluation of an intervention program to prevent hospital-acquired catheter-associated urinary tract infections in an ICU in a rural Egypt hospital - Amine, Amira Ezzat Khamis; Helal, Mohamed Omar Mohamed; Bakr, Wafaa Mohamed Kamel (German Medical Science GMS Publishing House, 2014)
[english] Aim: Catheter associated urinary tract infections (CAUTI) are the most common hospital-acquired infection in ICUs. The aim of this study was to estimate the effectiveness of an intervention program by implementing urinary catheter bundle elements to reduce the CAUTI frequency in an ICU. Methods: The intervention study was conducted over a period of onths. During a pre-intervention phase, the base line catheter associated CAUTI incidence rates were determined and compared with the incidence rates during the post-intervention phase. The compliance of health care staff with urinary catheter bundle elements was also measured. The implemented CAUTI prevention bundle consisted of hand hygiene, wearing personal protective equipment, use of disposable gloves, cleansing of urethral meatus prior to catheter insertion using sterile saline, assessment of catheter need, aseptic urine sampling technique, and correct draining bag positioning.Results: During the study period, 55 out of 77 patients were diagnosed with a CAUTI. The mean CAUTI incidence rate for the pre-intervention period was 90.12/1,000 catheter days and for the post intervention phase 65.69/1,000 catheter days. The CAUTIs rate was inversely proportional to insertion bundle elements and maintenance bundle elements compliance rate. This negative relationship was statistically significant only with maintenance bundle elements (p=0.042) (r=-0.828). The compliance rate of the ICU nurses to the bundle elements was raised to 100% during the last 2 months of the post intervention phase.Conclusion: Increased compliance to recommended catheter associated urinary tract infections preventive practices reduced the incidence of CAUTI in an ICU unit. It is simple and effective and is recommended as a part of patient safety culture.